Quasi-cylindrical waves on a dielectric-film-coated metal surface - Wang, Heming; Xin Chen; Wei, Siyuan; Fan Yang; Huimin Liao; Li, Zhi; Chen, Jianjun; Qihuang Gong (JOURNAL OF THE OPTICAL SOCIETY OF AMERICA B-OPTICAL PHYSICS, 2015)
In addition to surface plasmon polaritons (SPPs), quasi-cylindrical waves (CWs) are also important components of electromagnetic fields on metal surfaces. In this study, we present a closed-form expression for CW fields on a dielectric-film-coated metal surface. It is found that the effective refractive index of CWs roughly keeps unchanged when the coated dielectric film becomes thicker, while the effective refractive index of SPPs increases rapidly. These different responses are explained by referring to a waveguide perspective, in which the SPP and CW waves are, respectively, identified as a waveguide mode and superposition of radiation modes. The results and related analyses with the waveguide perspective explicitly show the different physical natures of SPPs and CWs. (C) 2015 Optical Society of America